Establishing pathological cut-offs of brain atrophy rates in multiple sclerosis. Issue 1 (22nd April 2015) - De Stefano, Nicola; Stromillo, Maria Laura; Giorgio, Antonio; Bartolozzi, Maria Letizia; Battaglini, Marco; Baldini, Mariella; Portaccio, Emilio; Amato, Maria Pia; Sormani, Maria Pia
Abstract : Objective: To assess whether it is feasible to establish specific cut-off values able to discriminate 'physiological' or 'pathological' brain volume rates in patients with multiple sclerosis (MS). Methods: The study was based on the analysis of longitudinal MRI data sets of patients with MS (n=206, 87% relapsing–remitting, 7% secondary progressive and 6% primary progressive) and healthy controls (HC; n=35). Brain atrophy rates were computed over a mean follow-up of 7.5 years (range 1–12) for patients with MS and 6.3 years (range 1–12.5) for HC with the SIENA software and expressed as annualised per cent brain volume change (PBVC/y). A weighted (on the follow-up length) receiver operating characteristic analysis and the area under the curve (AUC) were used for statistics. Results: The weighted PBVC/y was −0.51±0.27% in patients with MS and −0.27±0.15% in HC (p<0.0001). There was a significant age-related difference in PBVC/y between HC older and younger than 35 years of age (p=0.02), but not in patients with MS (p=0.8). The cut-off of PBVC/y, as measured by SIENA that could maximise the accuracy in discriminating patients with MS from HC, was −0.37%, with 67% sensitivity and 80% specificity. According to the observed distribution, values of PBVC/y as measured by SIENA that could define a pathological range were above −0.52% with 95% specificity, above −0.46% with 90% specificity and above −0.40% with 80% specificity. Conclusions: Our evidence-based criteria provide values able to discriminate the presence or absence of 'pathological' brain volume loss in MS with high specificity. Such results could be of great value in a clinical setting, particularly in assessing treatment efficacy in MS.